Economics, Veterinary Service and Herd Health Programs - Steven C Henry (Kansas Agricultural Experiment Station Research Reports, 1982)
Among the many changes in the swine industry during the past two decades, the concept of "Herd Health Programs" came to be. Still a buzz word with poorly defined activities, "Herd Health Programs" are part of our industry. Just listen in the halls during producer or veterinary meetings -- we discuss getting one, already having one, offering one, getting into the business of delivering several of them -- and none of us is quite sure what "one" is and, most of all, what it's worth. There should be no surprise that neither of us, producer or veterinarian, really has the foggiest notion of the economics of such things. We're not primarily business people with cost/benefit analysis capabilities. We have both, however, just been initiated into the fact we must become analytical, economically astute or hire the job done for us. The answer to the question "how much is a Herd Health Program worth?" is not to be found in this presentation. I hope we can all think about it a little and maybe, with help, it will be a definable term in the future.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422